Control of a COVID-19 Outbreak in a Spanish Prison: Lessons Learned in Outbreak Control - Vicente-Alcalde, Nancy; Ruescas-Escolano, Esther; Franco-Paredes, Carlos; Tuells, José (Frontiers in Medicine, 2022)
The rapid spread of highly transmissible respiratory infections in carceral settings occurs due to their conglomerate nature. The COVID-19 pandemic has resulted in large outbreaks in jails and prisons in many settings. Herein, we describe an outbreak of SARS-CoV2 infection in a prison in Alicante, Spain. Prior to January 2021, testing for coronavirus infection was not widely available in jails and prisons nationwide. Offering of testing services in Spanish carceral facilities coincided with the deployment of COVID-19 vaccination in the larger community. However, COVID-19 vaccine role out of incarcerated individuals occurred later during the deployment plan. With the identification of the initial cases of this outbreak, two units of the facility were assigned for population management: one for inmates with a confirmed infection by positive PCR detection of SARS-COV-2 infection in nasopharyngeal swabs. Inmates with confirmed exposure and thus considered close contacts were placed in a second isolation unit. Functional quarantine was employed in some instances. A reactive testing strategy was instituted at baseline, and at 7 and 14 days of nasopharyngeal specimens by PCR. A total of 1,097 nasopharyngeal specimens were obtained for PCR testing during the outbreak, which lasted a total of 80 days between the index case the end of medical isolation of the last case. A total of 103 COVID-19 cases were identified during the outbreak. Of these, three inmates developed severe manifestations requiring hospitalization, and one died. were identified, among which there were three hospitalized and one deceased. Among cases and confirmed contacts, we conducted close clinical monitoring, symptom screening, and daily temperature checks. The implementation of these interventions along with early medical isolation of cases, quarantining of contacts, and interval testing to detect presymptomatic or asymptomatic cases were instrumental in containing this outbreak.